EFL Students’ Academic Buoyancy: Does Academic Motivation and Interest Matter? - Xu, Xin; Wang, Bin (Frontiers in Psychology, 2022)
The way students are treated by their teachers have been proven to play a paramount role in students’ performance. Either teachers’ academic buoyancy or academic motivation may change students’ mindset about learning a language, leading to facilitating this process or making it even more demanding than it seems. Considering that, it can be taken into account how important teachers’ academic buoyancy would be and its mediators such as academic motivation should draw precise attention to themselves. However, a few studies have been conducted about this pivotal role so far. To fill this gap, this review paper provides a glimpse at the underlying roles of academic buoyancy and academic motivation and interest. Furthermore, it presents the definitions and applications of each construct. Finally, some implications and future recommendations are put forward to enthusiastic scholars.